MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KREATIF DALAM MENULIS TEKS PUISI DI SMP - Poni Fera; Kamarudin Kamarudin; Rustam Rustam (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
This study aims to explain the implementation of the project based learning (PjBL) learning model in learning to write poetry texts. The research method used is a qualitative method, this type of research is a phenomenological research type, which is a study that seeks to articulate the "essences" of meaning in life experiences. Using a feminist perspective, the focus of this research is on their memory and life experiences. This research focuses on one main phenomenon (or concept or idea). Narrow the research into one idea to be explored and understood. This study produced several findings, namely (1) project based learning (PjBL) in learning to write poetry texts; (2) this learning model is difficult to implement in learning to write poetry texts in a limited time; (3) this learning model produces satisfactory student scores. Based on the discussion, it can be concluded that (1) the project based learning (PjBL) learning model can be implemented well and easily with additional learning time; and (2) the results of the implementation of the project based learning (PjBL) model in the form of the value of the project work, namely literary works of poetry showed very satisfactory results.